Digital Driven Green Entrepreneurship: A Systematic Review of Plastic Waste Reduction Strategies by MSMEs in Indonesia - Delyardi Nur; Reza Febrina Agustin (Yayasan Edukasi Cakrawala Nusantara, 2026)
The main problem in this study is the high dependence of MSMEs in the beverage sector in Indonesia on the use of single-use plastic packaging, which cumulatively contributes significantly to environmental pollution. Low environmental awareness, lack of understanding of waste management, and limited access to sustainable packaging solutions make MSME business practices not in line with sustainability principles. This study aims to identify strategic approaches through green entrepreneurship that can be implemented by beverage sector MSMEs to reduce the environmental impact of plastic use. The method used was Systematic Literature Review (SLR) based on the PRISMA protocol and bibliometric analysis using VOSviewer, by searching for relevant articles from scientific databases within the period 2019-2024. The results show that the green entrepreneurship approach, involving green innovation, regulatory support, and environmental literacy, is proven to significantly and positively support the transformation of MSMEs towards more sustainable business practices. This finding reinforces the urgency of implementing green entrepreneurship as a strategic solution to the plastic waste problem while strengthening the contribution of MSMEs to the national green economy.